Managing Positive Change: Emotions and Communication Following Acquisitions - Harikkala-Laihinen Riikka (Taylor & Francis (Commercial Publisher), 2025)
This article takes a positive organizational scholarship lens to change management and explores what is the relationship between emotions and communication in managing positive change. Through an abductive study, it suggests a framework of positive post-acquisition change, which centres on interaction in the generation of positive emotions. The framework is built based on a Finnish – German merger completed in late 2013 and substantiated through a German – Finnish acquisition completed in early 2017. Based on the findings, positive emotions can enhance employee identification with the post-acquisition organization as well as increase motivation and engagement in change. Conversely, negative emotions are likely to cause protectionist, change-resistant behaviour. Whereas top-down communication is essential in ensuring day-to-day functions, interaction enables the creation of positive emotions and thereby engages employees in change-congruent behaviour.